PROFILES OF MATHEMATICS COMMUNICATION ABILITIES IN GROUP MATERIAL BASED ON GPA SCORE OF MATHEMATICS TEACHER CANDIDATE STUDENTS - Akhyar Tawil (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
The objective of the research is to discover the profiles of Mathematics communication abilities of students with high GPA score and students with medium GPA score and its comparison. The research was conducted by revealing the students’ Mathematics communication abilities through Mathematics communication ability test with group problem. Based on the test results, the students then interviewed to confirm the students’ answers and to obtain deeper data. The research was qualitative research with descriptive approach. The subjects of the research were the students of academic year 2014 of Mathematics Education Program at FKIP Untad, consisted of two students with high GPA score and two students with medium GPA score. The results of the research reveal that: (1) the students with high GPA score (MIT) have Mathematics communication abilities in solving group problem: Representing the intention of the question by writing information which was known and asked in a form of point by point by using short sentence and able to make symbol in accordance with the information. The two subject writing the answer to solve group problem question quite complete started from known and asked information from the question until the stages of problem solving. However, the two subjects had difference in writing reason in the stages of group problem solving answer. Subject MIT1 was quite consistent in writing the reasons in several stages of solving which the subject made but subject MIT2 tended to not writing the reason in most of the answer stage of question solving, using all the symbols which often used in group material in solving test question, re-explaining the answer of question solving stage by stage according to the answer which the subject wrote. The subject explained each solving stage with reasons from the stage; (2) the students with medium GPA score (MIS) had Mathematics communication abilities in solving group problem. Subject MIS1 tended to write the information which was known and asked in one sentence, while subject MIS2 wrote information which was known and asked through point by point. The two subjects were able to make symbols in accordance with the information which was known from the question, the two subject writing the answer of group problem solving incompletely in the stages, able to write the reason in several stage of solving answer, very lack in using symbols which usually used in group material, even several sentences which could be written in from of Mathematics symbol were not written in from of symbol by the subjects. Subject MIS1 re-explaining the answer of test question shortly and not in details in the stages, while subject MIS2 re-explaining the answer of test question through stages by stages in accordance with the answer which the subject had written and explained each reason in the steps